A New Application of School Budgets: Utilization Perspective - Diky Paramitha; Dwirini Dwirini; Zulkifli Sultan (Jurnal Mirai Management, 2023)
The School Activity Plan and Budget Application (ARKAS) is an information system that utilizes advances in Information Communication and Technology (ICT) to carry out the functions of the system of budgeting, implementing, administering and accountability of school operational assistance funds in primary and secondary education units nationally. This application was created to handle school financial management problems whose process is still done manually and has not been integrated with one system. With the support of integrated technology, schools can use it to manage finances and the Ministry of Education and Culture and Technology can monitor the accountability of each school. The purpose of this study is to analyze the use of ICT for school budget management. Data collection in this study through observation, interviews and documentation. Data analysis techniques are carried out by data reduction, data presentation, data analysis and conclusions to the results. From the research, it was concluded that the average use of ICT in each region in managing school installments is still low so that the decision of the Ministry of Education and Culture in creating applications to integrate the system is very appropriate to increase the use of ICT in managing school budgets Keywords: ICT, ARKAS